Passing of Mr. Nicasio M. Bonao - Bonao, Nicasio M. (Animo Repository, 2022)
The office of the chancellor announced to the Lasallian community with deep sadness the passing of Mr. Nicasio M. Bonao retired former Senior System Administrator of Information Technology Services Office.